MEMBANGUN HUKUM INDONESIA YANG BERKARAKTER - Muhammad Ali Mansyur (UNISSULA, 2014)
Building the Indonesian character law means building the law of the values of the personality of the Indonesian nation, Pancasila (the five principles). The embodiment of the values of the principles: divinity, humanity, unity, democracy, and social justice animate and enliven the devolepment of national laws of Indonesia, able to respond the process and the changes that occur without leaving its legal indentity, Pancasila